Deborah Blum: „Mózg i płeć. O biologicznych różnicach między kobietami i mężczyznami”. Przekł. E. Kołodziej-Józefowicz. Warszawa, Prószyński i S-ka 2004, ss. 344 - Ecler-Nocoń, Beata (Chowanna, 2006)
recenzja